The Impact of Praying on Stress and Anxiety in Mothers with Premature Infants Admitted to NICU - Maryam Sharifnia; Mohamed Hasan Hasanzadeh; Seyed Morteza Asadi Kakhaki; Seyed Reza Mazlom; Soheila Karbandi (Mashhad University of Medical Sciences, 2016)
Background: Neonatal mortality, prematurity, and congenital disorders, known as crisis, are unexpected stressful events causing extreme maternal stress. According to the literature, about 28-70% of the mothers have a high degree of psychological stress. Among different treatments, praying as a complementary religious approach is the most common source that people use in difficult conditions. Regarding this, the aim of the present study was to determine the effect of praying on anxiety and stress in mothers with premature neonates admitted to the Neonatal Intensive Care Unit (NICU). Methods: This clinical trial was conducted on 60 mothers with premature neonates. The participants were randomly divided into the intervention and control groups. In the intervention group, praying was performed one day after the presence of the mother in the NICU for 7 days. The tools employed in this study included the demographic characteristics and subject selection forms, depression, anxiety, and stress scale, as well as Symptom Checklist-90-R and prayer questionnaires. The validity and reliability of these tools were approved using content validity and internal consistency, respectively. Data analysis was performed by independent and paired t-tests as well as ANOVA through SPSS version 11.5. Results: The two groups were matched in terms of all maternal demographic and neonatal characteristics, except neonatal birth weight (P=0.045). As the results demonstrated, there was a statistically significant difference between the intervention and control groups in terms of their anxiety scores (P=0.02); however, the difference was not significant after one month following the intervention (P=0.076). Nevertheless, no statistically significant difference was observed between the stress scores of the two groups. Conclusion: As the findings of the current study revealed, praying can be effective in reducing the maternal anxiety.